EVALUATION OF THE KARTU TANI PROGRAM IN SUBSIDIZED FERTILIZERS DISTRIBUTION IN BANYUMAS REGENCY, CENTRAL JAVA PROVINCE - Imwadia Ramadhoni; Berliana Prilli Nomita (Fakultas Politik Pemerintahan IPDN, 2022)
Abstract The Governor of Central Java Province initiated the Kartu Tani Program to realize the distribution, control, and supervision of subsidized fertilizers for farmers. However, there are still problems with implementing this program from the farmers, KPL (Complete Fertilizer Kiosk) and distributors, related agencies, and third parties, BRI Bank. The problems include the scarcity of subsidized fertilizers, delays in fertilizer distribution, inaccuracy targeting, and overpriced provision. So, this article proposes to discuss the Kartu Tani Program evaluation in Banyumas Regency. Using the Quasi Qualitative Design (QQD), the data was obtained from various documents, observations, and interviews. This article also used Manual Data Analysis Procedure (MDAP). Based on the evaluation, after the existence of the Kartu Tani, farmers experienced many conveniences, including the relatively low price of fertilizer, the fertilizer quota, and the specific location of the fertilizer seller based on residents and farmer groups. Not only farmers, fertilizer sellers, and distributors also benefit from the Kartu Tani to make subsidized fertilizer reports from sales to distributors. On the other side, we show that many complaints regarding the Kartu Tani are still entered into the Banyumas Regency complaint hotline, but most of these complaints can be resolved. The Department of Agriculture and Food Security of Banyumas Regency commits to optimally implementing the Kartu Tani Program as the right solution for subsidized fertilizers distribution to farmers in the Banyumas Regency. Keywords: Fertilizer distribution, Kartu Tani, policy evaluation, subsidized fertilizers.